Etude de performances biologiques du loup d’écloserie Dicentrarchus labrax en grossissement intensif nourri avec un aliment semi-humide - GUERBEJ, Hamadi (INSTM Bulletin : Marine and Freshwater Sciences, 1996)
The study of biological performances of sea-bass Dicentrarchus labrax fed with a semi-dry food during the phase of growth was conducted in the Center of Aquaculture in Monastir (Tunisia). It lasted 383 days and it has revealed that the rate of survival is 70% and that of the specific growth is 0,47. The registered values of the high rates of feeding transformation, probably reflect the assimilation problems of the semi-dry food, the nutritive composition of wich (proteine lipide and glucide) is variable in terms of quality and quantity.